Mergers as Reallocation - Jovanovic, Boyan; Rousseau, Peter L. (The Review of Economics and Statistics, 2008)
We model merger waves as reallocation waves, and argue that mergers spread new technology in a way that is similar to that of the entry and exit of firms. We focus on two periods: 1890–1930, during which electricity and the internal combustion engine spread through the U.S. economy, and 1970–2000—the Information Age. As the model implies, reallocation did rise during both epochs. The model also implies that exits should lead mergers during a transition, but this seems to have happened more emphatically in the electrification epoch.